Dynamic changes in liver volume calculated using a three‐dimensional visualisation system after microwave ablation of hepatocellular carcinomas. Issue 7 (28th April 2022) - Dong, Linan; Cheng, Zhigang; Liu, Fangyi; Yu, Xiaoling; Han, Zhiyu; Luo, Yanchun; Xu, Hongli; Chen, Rendong; Huang, Chongfei; Yu, Jie; Liang, Ping
Abstract: Objectives: To investigate the changes in liver volume and function after microwave ablation (MWA) of hepatocellular carcinomas (HCCs). Materials and Methods: We retrospectively analysed 76 patients with 106 nodules who underwent MWA for HCCs ≤5 cm between January 2015 and September 2017. Liver and ablation volumes were calculated using a three‐dimensional visualisation system on MRI. Multiple regression analysis was used to estimate the association between the ablation volume and liver volume changes. Deformable image registration (DIR) was performed to confirm the influence of liver volume changes on curative effect evaluation after ablation. Results: The initial liver and tumour volumes were 1262.1 ± 259.91 cm 3 (range: 864.9–1966.8) and 2.5 cm 3 (interquartile range [IQR]: 1.3–8.8), respectively. Compared to the initial liver volumes, the entire live volume (ELV) increased by 10.1% ± 8.93% (range: −4.9% to 46.68%) on the 3rd day after ablation. Subsequently, it recovered to initial level at the 3rd month and maintained its level during the 1‐year follow‐up. The median total ablation volume was 34.9 cm 3 (IQR: 20.4–65.4) on the 3rd day after ablation, which decreased by 71.2% (IQR: 57.4%–78.1%) 1 year after ablation. Alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin (T‐Bil) peaked within 3 days after MWA and recovered to normal within 1 month. The ablation volume proportion of the ELV was an independent risk factor for the increase in the ELV and AST, ALT and T‐Bil levels within 3 days after ablation. When DIR was conducted to fuse ablation zone and tumour, the reshaped tumour volumes were enlarged by 40% because of the increase in ELV. Conclusions: MWA of HCCs based on the Milan criteria could induce temporary increases in ELV and RLV within 3 days after ablation, but both parameters recovered to initial levels 3 months after ablation. This indicates that MWA of early‐stage HCCs would not lead to liver volume loss and could potentially protect liver function. The liver cannot be treated as an incompressible organ after ablation, and the appropriate deformation constraint should be designed for DIR to evaluate ablation margin accurately.